Regulation of ABC Drug Efflux Transporters in Human T-Cells Exposed to an HIV Pseudotype - Whyte-Allman, Sana-Kay; Kaul, Rupert; Bendayan, Reina (Frontiers in Pharmacology, 2021)
ATP-binding cassette (ABC) drug efflux transporters could contribute to low intracellular concentrations of antiretroviral drugs in HIV-1 cell reservoirs and sanctuary sites. Furthermore, the functional expression of these transporters could be induced in activated T-cells. Therefore, we investigated the expression of ABC drug efflux transporters in human T-cells exposed to an HIV pseudotype virus (pHIVNL4-3), and further examined the potential involvement of the mammalian target of rapamycin (mTOR) signaling pathway in regulating their expression following exposure to pHIVNL4-3. Additionally, we investigated the contribution of the drug efflux transporters to the inflammatory response following pHIVNL4-3-induced T-cell activation. Human peripheral blood mononuclear cells (PBMCs) were exposed to HIV-1 envelope glycoprotein gp120IIIB, pHIVNL4-3 and/or mTOR inhibitors. The expression of ABC transporters, T-cell activation marker CD69, mTOR and pHIVNL4-3 was assessed in CD4+ T-cells by Flow cytometry. mRNA and protein levels of proinflammatory cytokines (IL6, TNFα and INFγ) were examined in PBMCs by qPCR and ELISA analyses, respectively, following exposure to pHIVNL4-3 with or without inhibitors of mTOR or ABC transporters. The expression of ABC transporters (P-glycoprotein, breast cancer resistance protein and multi-drug resistance associated protein-1) was significantly increased in CD4+ T-cells exposed to pHIVNL4-3. Treatment with mTOR inhibitors attenuated pHIVNL4-3-induced transporter expression, as well as mRNA and protein levels of IL6, TNFα and INFγ. Additionally, inhibition of P-gp or MRP1 activity resulted in lower concentrations of proinflammatory cytokines in supernatants of PBMC exposed to pHIVNL4-3. Herein we present novel data demonstrating that upregulation of ABC drug efflux transporters could involve the mTOR signaling pathway in CD4+ T-cells exposed to an HIV pseudotype. These transporters could limit antiretroviral drug penetration in HIV target T-cells. Furthermore, ABC transporters could potentially contribute to HIV-associated proinflammatory cytokine secretion.